Reactive Oxygen Species Responsive Polymers for Drug Delivery Systems - Gao, Fengxiang; Xiong, Zhengrong (Frontiers in Chemistry, 2021)
Reactive oxygen species (ROS) play an essential role in regulating various physiological functions of living organisms, however, as the concentration of ROS increases in the area of a lesion this may undermine cellular homeostasis, leading to a series of diseases. Using cell-product species as triggers for targeted-regulation of polymer structures and activity represents a promising approach for the treatment. ROS-responsive polymer carriers allow the targeted delivery of drugs, reduce toxicity and side effects on normal cells, and control the release of drugs, which are all advantages compared with traditional small-molecule chemotherapy agents. These formulations have attracted great interest due to their potential applications in biomedicine. In this review, recent progresses on ROS responsive polymer carriers are summarized, with an focus on the chemical mechanism of ROS-responsive polymers and the design of molecular structures for targeted drug delivery and controlled drug-release. Meanwhile, we discuss the challenges and future prospects of its applications.